Studi Sanitasi Lingkungan Pemukiman Masyarakat di Kelurahan Kalebajeng Kecamatan Bajeng Kabupaten Gowa - Achmad Hilal (Journal of Health Quality Development, 2021)
An environment with poor sanitation will have a negative impact on the health of the community around the environment, this study aims to understand the existing conditions of environmental sanitation in community settlements in Kalebajeng Village, Bajeng District, Gowa Regency. The method used is descriptive analysis with a survey approach, analysis to describe the characteristics of each research indicator in the form of frequency distribution and histogram. The results of the study indicate that waste control in the residential environment of the Kalebajeng Village, Bajeng District, Gowa Regency is in the good category. Wastewater control in the residential community in Kalebajeng Village, Bajeng District, Gowa Regency, in the aspect of providing sewers is in good category.